PEMANFAATAN PUPUK ORGANIK UNTUK MENINGKATKAN KESUBURAN TANAH PADA PERTANAMAN KACANG TANAH - Nurmi, Nurmi; Azis, Arief (Universitas Negeri Gorontalo, 2023)
The purpose of the service is to increase soil fertility through the use of organic chicken manure fertilizer and roasted husks in peanut plantings. The method used in this service is providing education about the role of organic fertilizer in improving soil properties, and conducting direct visits to experimental plots of peanut plants that were given organic fertilizer from chicken manure and roasted husks. The results of the service are in the form of fertilization technology transfer, in this case the use of organic chicken manure fertilizer and roasted husks which are transferred from lecturers to farmers as partners in the form of counseling and demonstration plot visits. Partners play an active role in this service, especially in technical implementation in the field. The community service program carried out was well received by farmers. Farmers are very optimistic that they can apply what they have obtained in this community service activity, because this technology is very easy to apply. Organic chicken manure fertilizer and roasted husks are very easy to obtain at service locations. Once fermented, it can be directly applied to farmers' crops. During the demonstration plot visit, farmers directly observed the growth and yield of peanut plants in each experimental plot. The growth and yield of peanut plants in experimental plots that used organic fertilizer were much better than those that did not use organic fertilizer.